2011
DOI: 10.1007/s00221-011-2558-6
|View full text |Cite
|
Sign up to set email alerts
|

Complementary gain modifications of the cervico-ocular (COR) and angular vestibulo-ocular (aVOR) reflexes after canal plugging

Abstract: To determine whether the COR compensates for the loss of aVOR gain, independent of species, we studied cynomolgus and rhesus monkeys in which all six semicircular canals were plugged. Gains and phases of the aVOR and COR were determined at frequencies ranging from 0.02 to 6 Hz and fit with model-based transfer functions. Following canal plugging in a rhesus monkey, the acute stage aVOR gain was small and there were absent responses to thrusts of yaw rotation. In the chronic state, aVOR behavior was characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 68 publications
(128 reference statements)
1
22
0
Order By: Relevance
“…In contrast, many of the neurons that control balance (Nyberg-Hansen and Mascitti, 1964; Petras, 1967; Peterson et al, 1978; Carleton and Carpenter, 1983; Carpenter, 1988) and influence blood pressure (Uchino et al, 1970; Yates et al, 1993; Kerman and Yates, 1998) are located caudally in the vestibular nucleus complex. In addition, the major components of vestibulo-ocular reflexes are dependent on inputs from semicircular canals (Money and Scott, 1962; Suzuki and Cohen, 1964, 1966; Baker et al, 1982; Hess et al, 2000; Sadeghi et al, 2009; Yakushin et al, 2011). Although data are limited, at least some cognitive responses related to vestibular inputs also appear to require inputs from semicircular canals (Muir et al, 2009).…”
Section: Compensation Following Bilateral Vestibular Dysfunction: Stumentioning
confidence: 99%
“…In contrast, many of the neurons that control balance (Nyberg-Hansen and Mascitti, 1964; Petras, 1967; Peterson et al, 1978; Carleton and Carpenter, 1983; Carpenter, 1988) and influence blood pressure (Uchino et al, 1970; Yates et al, 1993; Kerman and Yates, 1998) are located caudally in the vestibular nucleus complex. In addition, the major components of vestibulo-ocular reflexes are dependent on inputs from semicircular canals (Money and Scott, 1962; Suzuki and Cohen, 1964, 1966; Baker et al, 1982; Hess et al, 2000; Sadeghi et al, 2009; Yakushin et al, 2011). Although data are limited, at least some cognitive responses related to vestibular inputs also appear to require inputs from semicircular canals (Muir et al, 2009).…”
Section: Compensation Following Bilateral Vestibular Dysfunction: Stumentioning
confidence: 99%
“…Both reflexes are indeed quite plastic, in the sense that they adapt to perturbations and changes of input. In laboratory settings, it has been observed that the VOR and COR adapt to experimentally perturbed visual and vestibular input (Schweigart et al 2002;Rijkaart et al 2004;Montfoort et al 2008;Yakushin et al 2011). However, little is known about the adaption of the reflexes to perturbed cervical input.…”
Section: Introductionmentioning
confidence: 99%
“…The early loss of response is probably due to detachment of the cupula from the roof of the ampulla, with reattachment at a later time, as found in the toadfish (Rabbitt et al 1999, 2009). The changes in gain over time in the toadfish are similar to responses to sinusoidal oscillation in the rhesus monkeys (Yakushin et al 2011). As our results demonstrate, there were no changes in spatial orientation of the canal responses after canal plugging, whether from single canals or from all six canals.…”
Section: Discussionmentioning
confidence: 69%
“…The responses obtained within the first week after canal plugging (acute state) were low in some animals, but they recovered to levels predicted by the model of the aVOR after several weeks (chronic state) (Yakushin et al 2011). The early loss of response is probably due to detachment of the cupula from the roof of the ampulla, with reattachment at a later time, as found in the toadfish (Rabbitt et al 1999, 2009).…”
Section: Discussionmentioning
confidence: 99%